Imeglimin increases glucose‐dependent insulin secretion and improves β‐cell function in patients with type 2 diabetes. Issue 6 (25th March 2015) - Pacini, G.; Mari, A.; Fouqueray, P.; Bolze, S.; Roden, M.
Abstract : Aims: To assess the glucose‐stimulated insulin secretion effect of imeglimin in patients with type 2 diabetes. Methods: We conducted a double‐blind, randomized, placebo‐controlled study in 33 patients with type 2 diabetes [glycated haemoglobin 6.8 ± 0.1% (51 mmol/mol)], who were drug‐naïve or withdrawn from their previous metformin monotherapy for 2 weeks and received imeglimin 1500 mg twice daily or placebo for 1 week. Glucose‐stimulated insulin secretion was assessed using a hyperglycaemic clamp. The primary endpoint was insulin secretion as defined by total insulin response [incremental area under the curve (iAUC)0–45 min ] and insulin secretion rate (ISR) calculated from C‐peptide deconvolution. β‐cell glucose sensitivity at steady state (second phase: 25–45 min), hepatic insulin extraction and insulin clearance were also calculated. Results: Imeglimin treatment for 7 days raised the insulin secretory response to glucose by +112% (iAUC0‐45, p = 0.035), first‐phase ISR by +110% (p = 0.034) and second‐phase ISR by +29% (p = 0.031). Imeglimin improved β‐cell glucose sensitivity by +36% (p = 0.034) and tended to decrease hepatic insulin extraction (−13%; p = 0.056). Imeglimin did not affect glucagon secretion. Conclusions: In patients with type 2 diabetes, imeglimin improves β‐cell function, which may contribute to the glucose‐lowering effect observed with imeglimin in clinical trials.